National Ambulatory Medical Care Survey, 1985 ([Verlag nicht ermittelbar], 1989)
The National Ambulatory Medical Care Surveys (NAMCS) supply data on ambulatory medical care provided in physicians' offices. The 1985 survey, the tenth in a series of annual surveys, contains information from approximately 2,879 physicians. Data are available on the number of office visits by the patient, the nature and length of the visits, the patient's problem, the physician's diagnosis, and the kinds of diagnostic and therapeutic services rendered. Information is also included on the physician's specialization, type of practice, and geographical location. Demographic information on patients was also collected.